PPHM corrugated pipe and preparation method thereof
By using modified mica sheets and carbon fibers in PPHM bellows, combined with compatibility agents and low-temperature resistant agents, the interface combination and formation of a three-dimensional network structure is enhanced, and the problem of performance of bellows in low-temperature environments is solved, and the mechanics is improved Performance and impact resistance.
Patent Information
- Application Number
- CN202510001006.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-02-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The performance of existing PPHM corrugated pipes is degraded in low temperature environments, and the interface bond between inorganic fillers and polypropylene resin is poor, resulting in the inability to effectively transmit stress, affecting the overall mechanical properties and impact resistance of the pipeline.
Modified mica sheets and modified carbon fibers are used to co-dopize, and compatible agents, low-temperature resistant agents and antioxidants are used to enhance the interface bonding strength through modification treatment, chemical bonding or physical adsorption, to form an orderly distributed structure and A three-dimensional network structure that supports each other.
It improves the overall mechanical properties and impact resistance of polypropylene resin, enhances the toughness and stability of corrugated pipes in low temperature environments, and ensures the stability and safety of the pipeline system.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of polymer materials, and more specifically, to a PPHM bellows and a preparation method thereof. Background Art
[0002] PPHM corrugated pipe, especially PPHM double-wall corrugated pipe, is a pipe with excellent performance, which is used in many fields such as municipal drainage, sewage, and farmland irrigation. PPHM corrugated pipe uses modified polypropylene as the main raw material, which is a polymer material that has been specially modified, giving PPHM corrugated pipe a series of excellent properties. In the municipal drainage and sewage system, PPHM double-wall corrugated pipe not only has to bear the static load from the ground, such as the weight of soil and buildings, but also has to deal with the dynamic load generated by the frequent passage of heavy vehicles. In addition, the pressure of the building foundation on the soil and possible uneven settlement are also challenges that PPHM corrugated pipes need to face. These complex stress conditions require that PPHM corrugated pipes must have good comprehensive performance to ensure the stability and safety of the pipeline system.
[0003] The winter temperature in the north is low, which puts higher requirements on the comprehensive performance of PPHM bellows. In low temperature environment, many materials will become brittle and easy to break. Therefore, it is urgent to develop a new preparation method to balance the various properties of PPHM bellows, especially to maintain relatively good performance in low temperature environment.
[0004] The patent application document with publication number CN101983982A discloses a raw material composition for preparing large-diameter polypropylene double-wall corrugated pipes, with a mass ratio of: 100 parts of polypropylene resin, 5-50 parts of inorganic filler, and 5-20 parts by mass of interface improver. The inorganic filler is selected from one of carbon black, montmorillonite, calcium carbonate, calcium sulfate, magnesium sulfate, silicon dioxide, and titanium dioxide; the interface improver is selected from 1-2 of silane coupling agent, titanate coupling agent, and polypropylene grafted maleic anhydride.
[0005] The large-diameter polypropylene double-wall corrugated pipe in this patent application document is made by directly physically blending the polypropylene resin, inorganic filler and interface improver. It is difficult to ensure a good interface bonding between the inorganic filler and the polypropylene resin, which will result in that when the corrugated pipe is subjected to external force, the stress cannot be effectively transferred from the resin matrix to the filler, thereby failing to fully exert the reinforcing and toughening effects of the filler. Summary of the invention
[0006] In order to ensure that the PPHM corrugated pipe has a certain strength and good impact resistance, the present application provides a PPHM corrugated pipe and a preparation method thereof.
[0007] In the first aspect, the present application provides a PPHM bellows, which adopts the following technical solution: A PPHM corrugated pipe, comprising 100 parts by mass of polypropylene resin, 4 to 10 parts by mass of mica sheets, 7 to 12 parts by mass of carbon fibers, 10 to 15 parts by mass of a compatibilizer, 5 to 15 parts by mass of a low-temperature resistant agent, and 0.8 to 1 part by mass of an antioxidant; The mica sheet is a modified mica sheet, and the carbon fiber is a modified carbon fiber; the low temperature resistant agent is at least one of ethylene-vinyl acetate copolymer and styrene-butadiene-styrene block copolymer; The preparation method of the compatibilizer comprises the following steps: uniformly mixing polypropylene powder, dibutyl maleate, hydroxyethyl acrylate, potassium persulfate and a solvent, heating to 70-80° C., reacting for 2-4 hours, cooling, solid-liquid separation, washing, and drying to obtain the compatibilizer, wherein the mass ratio of the polypropylene powder, dibutyl maleate and hydroxyethyl acrylate is 1:0.2-0.4:0.2-0.4; Preferably, the amount of potassium persulfate used is 0.7% to 1% of the total mass of dibutyl maleate and hydroxyethyl acrylate.
[0008] Preferably, the low temperature resistant agent comprises ethylene-vinyl acetate copolymer and styrene-butadiene-styrene block copolymer, and the mass ratio of the ethylene-vinyl acetate copolymer to the styrene-butadiene-styrene block copolymer is 1-2:3-4.
[0009] The beneficial effects are as follows: first, by using carbon fiber and mica flakes for co-doping, it is helpful to promote the molecular chains in the polypropylene resin to be oriented and form an orderly distribution structure. The layer structure of the mica flakes builds a structure similar to a small "platform" inside the polypropylene resin and determines a relatively fixed position. Some carbon fibers can be arranged along the distribution of the mica flakes or between the mica flakes in a relatively stable spatial position and attached to the layers of these mica flakes, which not only helps the carbon fibers to form an orderly distribution structure in the polypropylene resin, but also helps to form a three-dimensional network structure that supports and cross-links each other. In particular, when the polypropylene resin is subjected to external force, the mica flakes can support the carbon fibers from the side or bottom to prevent the carbon fibers from being excessively bent, deformed or lodging due to the force, and can also effectively disperse and transmit stress to avoid stress concentration in a local area, thereby reducing the possibility of damage due to excessive local force, thereby improving the overall mechanical properties and impact resistance of the polypropylene resin.
[0010] Secondly, by modifying the mica flakes and carbon fibers, the mica flakes and carbon fibers can be more evenly dispersed in the polypropylene matrix, reducing agglomeration, and can also undergo a certain degree of chemical bonding or strong physical adsorption with the polypropylene resin and the compatibilizer, greatly enhancing the interfacial bonding strength with the polypropylene resin. This is because the compatibilizer is polymerized from polypropylene powder, dibutyl maleate, and hydroxyethyl methacrylate. On the one hand, the polypropylene component in the compatibilizer has a good similar compatibility with the polypropylene resin. On the other hand, the active functional groups in dibutyl maleate and hydroxyethyl methacrylate can interact with the functional groups on the surface of the modified mica flakes and carbon fibers, playing the role of a "bridge" to promote better integration between the components and form a tightly combined and synergistic whole.
[0011] Finally, the addition of cryogenic agent gives polypropylene resin a certain flexibility, so that the corrugated pipe can adapt to the ground settlement and pipe bending that may occur in low temperature environment. This is because: when ethylene-vinyl acetate copolymer is added as a cryogenic agent, its molecular chain can be inserted between the molecular chains of polypropylene resin, and buffer the external force through its own bending, twisting and other movements, preventing stress from concentrating in the local area of the polypropylene molecular chain, thereby avoiding the brittle cracking of the corrugated pipe due to low temperature.
[0012] When the bellows is subjected to external forces such as bending, stretching or impact, the styrene-butadiene-styrene block copolymer can relieve the stress through the elastic deformation of the butadiene chain segment, so that the bellows maintains good toughness at low temperatures and reduces the possibility of rupture.
[0013] In addition, the addition of low-temperature resistant agent can also reduce the viscosity of the corrugated pipe during processing, so that the material can be extruded more smoothly through the extruder, and during the cooling process, through the movement and interaction of its molecular chains, it can adjust the crystallization behavior of the polypropylene resin, making it shrink more evenly and reducing the dimensional deviation caused by uneven local shrinkage, thereby improving the dimensional accuracy of the corrugated pipe and ensuring the stability and reliability of the product during installation and use.
[0014] Preferably, the method for preparing the modified mica sheet comprises the following steps: The mica flakes are uniformly dispersed in the sodium hexametaphosphate solution, and plasma treatment is performed for 10-20 minutes at a power of 200-300 W under an inert atmosphere. An initiator and propylene oxide are added, and the mixture is uniformly mixed. The mixture is heated to 70-90° C. and kept warm for 4-6 hours. The mixture is cooled, solid-liquid separation is performed, the mixture is washed, and the mixture is dried to obtain the modified mica flakes.
[0015] Preferably, the mass fraction of sodium hexametaphosphate in the sodium hexametaphosphate solution is 0.1% to 0.2%.
[0016] Preferably, the mass ratio of the propylene oxide to the mica flakes is 1:5-8.
[0017] Preferably, the initiator is potassium persulfate, and the amount of potassium persulfate used accounts for 0.5% to 0.75% of the mass of propylene oxide.
[0018] Beneficial effects: Propylene oxide undergoes polymerization reaction under the action of initiator and is grafted onto the surface of mica sheet by chemical bonding or physical adsorption, so that the modified mica sheet can not only be evenly distributed in the polypropylene resin, but also form a tighter interface with the polypropylene resin. When the bellows is subjected to external forces (such as stretching, bending, pressure, etc.), the stress will be evenly transferred to the mica sheet through the grafted polymer chain. The layer structure of the mica sheet can effectively disperse and share part of the stress, preventing the bellows from excessive deformation or breakage during the stretching process. In addition, since the grafted polymer chain segments improve the interface bonding between the mica sheet and the polypropylene resin matrix, the stress can be effectively transferred from the resin matrix to the mica sheet, so that the interface peeling between the mica sheet and the resin will not easily occur, but will cooperate to resist stretching, thereby improving the tensile strength of the bellows.
[0019] Preferably, the method for preparing the modified carbon fiber comprises the following steps: (1) Immersing the carbon fiber in a potassium permanganate solution, mixing for 2 to 4 hours, separating the solid and the liquid, washing, and then immersing the carbon fiber in a potassium persulfate solution, mixing for 1.5 to 2.5 hours, separating the solid and the liquid, washing, to obtain pretreated carbon fiber; (2) uniformly mixing acrylic acid, hydroxyethyl acrylate, styrene and a solvent to obtain a mixed emulsion; (3) Under an inert atmosphere, the pretreated carbon fiber, the redox initiator and the mixed emulsion are mixed evenly, the temperature is raised to 70-90°C, the temperature is kept for 4-6 hours, the temperature is lowered, the solid-liquid separation is performed, the mixture is washed and dried to obtain the modified carbon fiber.
[0020] Preferably, in step (1), the mass fraction of the potassium persulfate solution is 0.3% to 0.7%, and the mass ratio of the potassium persulfate solution to the carbon fiber is about 6 to 8:1.5.
[0021] Preferably, the molar concentration of the potassium permanganate solution is 6% to 12%, and the mass ratio of the potassium permanganate solution to the carbon fiber is 8 to 10:1.5.
[0022] Preferably, in step (3), the redox initiator is potassium persulfate and sodium sulfite, and the mass ratio of potassium persulfate to sodium sulfite is 1.5-3:1.
[0023] Preferably, in step (3), the amount of the redox initiator used is 1% to 1.5% of the total mass of acrylic acid, hydroxyethyl acrylate and styrene.
[0024] Preferably, the mass ratio of the carbon fiber to acrylic acid, hydroxyethyl acrylate and styrene is 1.5:0.04-0.06:0.1-0.2:0.1-0.15.
[0025] Beneficial effects: The modified carbon fiber is evenly dispersed in the polypropylene resin and has a high interface bonding strength with the polypropylene resin. When the corrugated pipe is subjected to external forces (such as stretching, bending, pressure, etc.), it can transfer stress along the stretching or bending direction. This effective transfer of stress helps to disperse the stress concentration in the corrugated pipe and improve the overall mechanical properties of the corrugated pipe.
[0026] Preferably, the content of vinyl acetate in the ethylene-vinyl acetate copolymer is 12% to 25%.
[0027] Preferably, the PPHM bellows further comprises 2 to 8 parts by mass of calcium chloride.
[0028] Preferably, the calcium chloride is obtained through the following pretreatment steps: S11: crushing and sieving calcium chloride, then immersing it in a silane coupling agent solution, mixing it for 1.5 to 2.5 hours, separating the solid from the liquid, drying it, and sieving it to obtain primary calcium chloride; S12: mixing primary calcium chloride with 20% to 25% by mass of bisphenol A epoxy resin solution for 40 to 60 minutes, drying, and dispersing to obtain pretreated calcium chloride.
[0029] Preferably, the mass fraction of the silane coupling agent solution is 1.5% to 2%.
[0030] Preferably, the silane coupling agent is KH-550.
[0031] Preferably, the mass ratio of the calcium chloride to the bisphenol A epoxy resin solution is 1:3-5.
[0032] Beneficial effects: Calcium chloride coated with bisphenol A epoxy resin can give full play to its filling performance, reduce the internal defects of the bellows, improve the density of the bellows, and form a stable and tight interface with the polypropylene resin, making the stress transfer between the two smoother and unimpeded. When the bellows is subjected to external force, the stress can be evenly dispersed in the entire polypropylene resin system, avoiding the occurrence of stress concentration, thereby significantly enhancing the overall mechanical properties and structural stability of the bellows.
[0033] In addition, the pretreated calcium chloride is interwoven and synergistic with the modified carbon fiber and modified mica sheets to further stabilize and strengthen the entire three-dimensional network structure. This interwoven structure enables the bellows to be subjected to external forces, whether tensile, compressive or bending stress, through the synergistic effect of the various components to efficiently transfer and disperse stress, effectively inhibiting the generation and expansion of cracks, thereby greatly improving the comprehensive mechanical properties, impact resistance and long-term stability of the bellows, providing it with reliable performance guarantees in complex and changeable engineering application environments.
[0034] Preferably, the PPHM bellows further comprises 0.5 to 1.5 parts by mass of propylene glycol.
[0035] Beneficial effects: The addition of propylene glycol can optimize the dispersion of modified carbon fiber and modified mica flakes in polypropylene resin, thereby strengthening the interfacial compatibility and bonding force with polypropylene resin. When the corrugated pipe is subjected to external force, the stress is efficiently transferred from the polypropylene resin to the reinforcing phase, giving full play to the mechanical enhancement efficiency of the reinforcing phase, thereby effectively inhibiting the initiation and expansion of cracks at the interface, giving the corrugated pipe more excellent toughness, impact resistance and long-term stability, so that it can maintain good performance in complex and changeable use environments, such as vehicle dynamic loads, building foundation pressure and possible uneven settlement faced by municipal drainage and sewage systems, and extend service life and reduce maintenance costs.
[0036] In a second aspect, the present application provides a method for preparing the above-mentioned PPHM bellows, comprising the following steps: S1: premixing a compatibilizer and a portion of polypropylene resin uniformly, then adding modified mica flakes, modified carbon fiber, a low temperature resistant agent and another portion of polypropylene resin, and mixing uniformly to obtain an extrudate; S2: Add the extrudate into the extruder and extrude, size, cool, cut and inspect the quality to obtain the PPHM corrugated pipe.
[0037] Preferably, in step S2, the extrudate is added into a twin-screw extruder and extruded, the screw speed is 180-200r / min, the barrel of the twin-screw extruder from the feed port to the extrusion die is sequentially set as Zone I, Zone II, Zone III and Zone IV, the temperature of Zone I is set to 155-165°C, the temperature of Zone II is set to 165-175°C, the temperature of Zone III is set to 175-185°C, the temperature of Zone IV is set to 185-195°C, vacuum sizing, the vacuum degree is maintained between -0.03Mpa and -0.05Mpa, air cooling and shaping, cutting, quality inspection, to obtain a PPHM corrugated pipe.
[0038] Preferably, in step S1, after adding the low-temperature resistant agent, a step of adding calcium chloride is also included.
[0039] Preferably, in step S1, after adding calcium chloride, the step of adding glycerol is also included.
[0040] In summary, this application has the following beneficial effects: 1. The present application adopts modified carbon fiber and modified mica sheet to be co-doped, and a certain amount of compatibilizer is compounded to promote the directional arrangement of molecular chains in polypropylene resin, forming an ordered distribution structure and a mutually supporting and cross-linked three-dimensional network structure, which can not only improve the overall mechanical properties of polypropylene resin, but also improve the impact resistance from two aspects: first, the ordered structure and the supporting effect of modified mica sheet on modified carbon fiber can effectively disperse and transfer stress, avoid stress concentration, and reduce damage due to excessive local force; second, the mica sheet and carbon fiber are modified to form chemical bonding or strong physical adsorption with polypropylene resin and compatibilizer to enhance the interface bonding strength, ensure that each component bears external force as a whole when impacted, which is conducive to stress transfer, thereby improving impact resistance.
[0041] 2. The cryogenic agents ethylene-vinyl acetate copolymer and styrene-butadiene-styrene block copolymer used in this application, the former molecular chains are interspersed between the molecular chains of polypropylene resin to buffer external forces and prevent stress concentration, and the latter relieves stress through elastic deformation of butadiene chain segments when subjected to force. The two together give the bellows flexibility, so that when the bellows is impacted, it can absorb and disperse energy through the movement and deformation of the molecular chains, avoid low-temperature brittle cracking, and effectively guarantee the impact resistance at low temperatures. The regulating effect of the cryogenic agent on the processing viscosity and crystallization behavior helps to form a high-dimensional precision bellows, and its stable size is conducive to better withstanding external forces during installation and use, indirectly improving the impact resistance.
[0042] 3. The present application compounds calcium chloride coated with bisphenol A epoxy resin to strengthen the interface bonding with polypropylene resin, so that it can fully fill microscopic gaps, transfer stress, and evenly distribute stress. It also stabilizes the three-dimensional network structure with modified carbon fibers and modified mica sheets like "nodes". Propylene glycol interacts with the molecular chains of polypropylene resin through hydrogen bonds, which enhances the activity of the molecular chains, thereby reducing the hardness to a certain extent. However, during stretching, it helps the molecular chains to be evenly stressed and resist deformation through "lubrication" and hydrogen bonding, thereby improving the tensile strength. This differentiated effect on hardness and tensile strength plays a unique role in PPHM bellows to optimize the comprehensive performance of the bellows. DETAILED DESCRIPTION
[0043] The present application is further described in detail below with reference to embodiments.
[0044] Unless otherwise specified, the raw materials used in the preparation examples, embodiments and comparative examples of the present application are all commercially available.
[0045] Ethylene-vinyl acetate copolymer, wherein the mass fraction of vinyl acetate is 12%, 18%, 25%, and 32%, purchased from Shanghai Hansi Chemical Co., Ltd.; Mica flakes, thickness 10~30nm, side length 4~8μm, purchased from Feiyue Stone Processing Factory, Hongqiao District, Tianjin; Carbon fiber, length 1~3mm, diameter 5~7μm, purchased from Jiangxi Shuobang New Material Technology Co., Ltd.; In the preparation example, the particle size distribution of the polypropylene powder is 100-300 μm, and it was purchased from Dongguan Taotao Plastic Raw Materials Co., Ltd.; In the examples and comparative examples, the particle size distribution of the polypropylene resin is 2-5 mm, and it was purchased from Dongguan Taotao Plastic Raw Materials Co., Ltd.; Maleic anhydride grafted polypropylene was purchased from Wuhan Huaxiang Kejie Biotechnology Co., Ltd.; Before use, the polypropylene resin was placed in a drying oven at 60°C for 5 h; Before use, antioxidant 1010 was placed in a drying oven at 60°C for 2 h; Before use, the mica sheets and carbon fibers were placed in a drying oven at 120°C for 4 hours.
[0046] Preparation Examples 1~3 Modified Mica Sheets Preparation Example 1 (1) adding 20 g of mica flakes to 200 g of a 0.1% sodium hexametaphosphate aqueous solution, ultrasonically dispersing for 30 min at a frequency of 20 Hz and an ultrasonic power of 200 W, then placing the mica flakes in a plasma treatment device, introducing argon gas, and treating at a power of 200 W for 20 min to obtain a pretreated mica flake dispersion; (2) In a reaction kettle equipped with a stirrer and a condenser, add the pretreated mica flake dispersion, heat to 50°C, then add 20 g of a 20% by mass propylene oxide aqueous solution, stir and mix evenly, heat to 60°C, slowly drop the potassium persulfate solution, stir and mix evenly after the addition is complete, then heat to 70°C, react for 6 h, cool, centrifuge, pour off the supernatant, wash twice with pure water, then transfer to a drying oven, and dry at 100°C for 3 h to obtain modified mica flakes.
[0047] The potassium persulfate solution is prepared by mixing 20 mg of potassium persulfate and 5 g of pure water.
[0048] Preparation Example 2 (1) 32 g of mica flakes were added to 300 g of a 0.2% sodium hexametaphosphate aqueous solution, and ultrasonically dispersed for 30 min at a frequency of 20 Hz and an ultrasonic power of 200 W. The mica flakes were then placed in a plasma treatment device, argon gas was introduced, and the treatment was performed at a power of 300 W for 10 min to obtain a pretreated mica flake dispersion. (2) In a reaction kettle equipped with a stirrer and a condenser, add the pretreated mica flake dispersion, heat to 50°C, then add 20 g of a 20% by mass propylene oxide aqueous solution, stir and mix evenly, heat to 60°C, slowly drop 30 mg of potassium persulfate solution, stir and mix evenly after the addition is complete, then heat to 90°C, react for 4 h, cool, centrifuge, pour off the supernatant, wash with pure water 3 times, then transfer to a drying oven, and dry at 100°C for 4 h to obtain modified mica flakes.
[0049] The potassium persulfate solution is prepared by mixing 30 mg of potassium persulfate and 5 g of pure water.
[0050] Preparation Example 3 (1) 28 g of mica flakes were added to 300 g of a 0.2% sodium hexametaphosphate aqueous solution, and ultrasonically dispersed for 30 min at a frequency of 20 Hz and an ultrasonic power of 200 W. The mica flakes were then placed in a plasma treatment device, argon gas was introduced, and the treatment was performed at a power of 240 W for 15 min to obtain a pretreated mica flake dispersion. (2) In a reaction kettle equipped with a stirrer and a condenser, add the pretreated mica flake dispersion, heat to 50°C, then add 20 g of a 20% by mass propylene oxide aqueous solution, stir and mix evenly, heat to 60°C, slowly drop 20 mg of potassium persulfate solution, stir and mix evenly after the addition is complete, then heat to 80°C, react for 5 h, cool, centrifuge, pour off the supernatant, wash with pure water 3 times, then transfer to a drying oven, and dry at 100°C for 4 h to obtain modified mica flakes.
[0051] The potassium persulfate solution is prepared by mixing 20 mg of potassium persulfate and 5 g of pure water.
[0052] Preparation Examples 4~6 Modified Carbon Fibers Preparation Example 4 (1) Take 180g of 8% potassium permanganate solution, add 0.5g of sodium dodecyl sulfate, stir and mix evenly, adjust the pH to 5.5 with 5% dilute sulfuric acid, add 30g of carbon fiber, and then place it in an ultrasonic device with a frequency of 20Hz and a power of 200W, mix for 2h, filter, wash twice with pure water, and then immerse in 150g of 0.5% potassium persulfate solution, immerse and stir for 1h, stirring at a speed of 100r / min, then add 10g of 0.5% potassium persulfate solution, continue to immerse and stir for 30min, filter, rinse with 5% dilute sulfuric acid, and then wash three times with pure water, and then spray with anhydrous ethanol to rinse, to obtain pretreated carbon fiber; (2) 0.8 g of acrylic acid, 4 g of hydroxyethyl acrylate, 2 g of styrene and 0.07 g of Tween 80 were added to 300 g of 40% ethanol aqueous solution in sequence, and stirred at 1000 r / min for 1 h to obtain a mixed emulsion; (3) Under an argon atmosphere, 30 mg of sodium sulfite, pretreated carbon fiber and mixed emulsion were stirred and mixed evenly. After the temperature was raised to 60 °C, potassium persulfate solution was slowly added dropwise. After the addition was completed, the temperature was raised to 80 °C and kept warm for 5 h. The mixture was filtered and washed three times with a mixture of ethanol and pure water in a volume ratio of 1:1. The mixture was then transferred to a vacuum oven and dried at 50 °C for 4 h. The mixture was then heated to 80 °C and dried at normal pressure for 1.5 h to obtain modified carbon fiber.
[0053] Wherein, in step (3), the potassium persulfate solution is prepared by mixing 50 mg of potassium persulfate and 10 g of pure water.
[0054] Preparation Example 5 (1) Take 200g of 6% potassium permanganate solution, add 0.5g of sodium dodecyl sulfate, stir and mix evenly, adjust the pH to 5 with 5% dilute sulfuric acid, add 30g of carbon fiber, and then place it in an ultrasonic device with a frequency of 20Hz and a power of 200W, mix for 2h, filter, wash twice with pure water, and then immerse in 160g of 0.3% potassium persulfate solution, immerse and stir for 1h, stirring at a speed of 100r / min, then add 10g of 0.3% potassium persulfate solution, continue to immerse and stir for 30min, filter, rinse with 5% dilute sulfuric acid, and then wash three times with pure water, and then spray with anhydrous ethanol to rinse, to obtain pretreated carbon fiber; (2) 1.2 g of acrylic acid, 2 g of hydroxyethyl acrylate, 3 g of styrene and 0.07 g of Tween 80 were added sequentially into 300 g of 40% ethanol aqueous solution, and stirred at 1000 r / min for 1 h to obtain a mixed emulsion; (3) Under an argon atmosphere, 25 mg of sodium sulfite, pretreated carbon fiber and the mixed emulsion were stirred and mixed evenly. After the temperature was raised to 60°C, the potassium persulfate solution was slowly added dropwise. After the addition was completed, the temperature was raised to 70°C and kept warm for 6 hours. The mixture was filtered and washed three times with a mixture of ethanol and pure water in a volume ratio of 1:1. The mixture was then transferred to a vacuum oven and dried at 50°C for 4 hours. The mixture was then heated to 80°C and dried at normal pressure for 1.5 hours to obtain modified carbon fiber.
[0055] Wherein, in step (3), the potassium persulfate solution is prepared by mixing 75 mg of potassium persulfate and 10 g of pure water.
[0056] Preparation Example 6 (1) Take 160g of 12% potassium permanganate solution, add 0.5g of sodium dodecyl sulfate, stir and mix evenly, use 5% dilute sulfuric acid to adjust the pH to 6, add 30g of carbon fiber, and then place it in an ultrasonic device with a frequency of 20Hz and a power of 200W, mix for 2h, filter, wash twice with pure water, and then immerse in 120g of 0.7% potassium persulfate solution, immerse and stir for 1h, stirring at a speed of 100r / min, then add 10g of 0.7% potassium persulfate solution, continue to immerse and stir for 30min, filter, rinse with 5% dilute sulfuric acid, then wash three times with pure water, and then spray with anhydrous ethanol to rinse, to obtain pretreated carbon fiber; (2) 1 g of acrylic acid, 3 g of hydroxyethyl acrylate, 2.4 g of styrene and 0.07 g of Tween 80 were added sequentially into 300 g of 40% ethanol aqueous solution, and stirred at 1000 r / min for 1 h to obtain a mixed emulsion; (3) Under an argon atmosphere, 28 mg of sodium sulfite, pretreated carbon fiber and mixed emulsion were stirred and mixed evenly. After the temperature was raised to 60°C, potassium persulfate solution was slowly added dropwise. After the addition was completed, the temperature was raised to 90°C and kept warm for 4 hours. The mixture was filtered and washed three times with a mixture of ethanol and pure water in a volume ratio of 1:1. The mixture was then transferred to a vacuum oven and dried at 50°C for 4 hours. The mixture was then heated to 80°C and dried at normal pressure for 1.5 hours to obtain modified carbon fiber.
[0057] Wherein, in step (3), the potassium persulfate solution is prepared by mixing 42 mg of potassium persulfate and 10 g of pure water.
[0058] Preparation Examples 7~9 Compatibilizer Preparation Example 7 (1) Add 100 g of polypropylene powder into 500 g of 1% sodium dodecyl sulfate solution, and then place it in an ultrasonic device at a frequency of 30 Hz and a power of 200 W for 2 h to obtain a polypropylene powder dispersion; (2) 20 g of dibutyl maleate, 40 g of hydroxyethyl acrylate, 1.2 g of Tween 80 and 300 g of 40% by mass ethanol aqueous solution were added into a reactor, and the mixture was stirred at 1000 r / min for 1 h to form a stable emulsion, thereby obtaining an emulsion; (3) Add the polypropylene powder dispersion to a reaction kettle equipped with an agitator, a thermometer and a condenser, start stirring, then slowly add the emulsion, continue stirring to mix evenly, raise the temperature to 60°C, and then slowly add the potassium persulfate solution. After the addition is complete, raise the temperature to 70°C and keep warm for 4 hours. During this period, stir continuously at 100 r / min. When the system begins to show a gel state, stop heating and stirring, cool naturally to room temperature, filter the gel product, wash it with pure water three times, transfer it to a vacuum drying oven, and dry it at 50°C to constant weight to obtain a compatibilizer.
[0059] The potassium persulfate solution is prepared by mixing 0.6 g of potassium persulfate and 20 g of pure water.
[0060] Preparation Example 8 (1) Add 100 g of polypropylene powder into 500 g of 1% sodium dodecyl sulfate solution, and then place it in an ultrasonic device at a frequency of 30 Hz and a power of 200 W for 2 h to obtain a polypropylene powder dispersion; (2) 40 g of dibutyl maleate, 20 g of hydroxyethyl acrylate, 1.2 g of Tween 80 and 300 g of 40% by mass ethanol aqueous solution were added into a reactor, and the mixture was stirred at 1000 r / min for 1 h to form a stable emulsion, thereby obtaining an emulsion; (3) Add the polypropylene powder dispersion to a reaction kettle equipped with an agitator, a thermometer and a condenser, start stirring, then slowly add the emulsion, continue stirring to mix evenly, raise the temperature to 60°C, and then slowly add the potassium persulfate solution. After the addition is complete, raise the temperature to 80°C and keep warm for 2 hours. During this period, stir continuously at 100 r / min. When the system begins to show a gel state, stop heating and stirring, cool naturally to room temperature, filter the gel product, wash it with pure water three times, transfer it to a vacuum drying oven, and dry it at 50°C to constant weight to obtain a compatibilizer.
[0061] The potassium persulfate solution is prepared by mixing 0.4 g of potassium persulfate and 20 g of pure water.
[0062] Preparation Example 9 (1) Add 100 g of polypropylene powder into 500 g of 1% sodium dodecyl sulfate solution, and then place it in an ultrasonic device at a frequency of 30 Hz and a power of 200 W for 2 h to obtain a polypropylene powder dispersion; (2) 30 g of dibutyl maleate, 30 g of hydroxyethyl acrylate, 1.2 g of Tween 80 and 300 g of 40% by mass ethanol aqueous solution were added into a reactor, and the mixture was stirred at 1000 r / min for 1 h to form a stable emulsion, thereby obtaining an emulsion; (3) Add the polypropylene powder dispersion to a reaction kettle equipped with an agitator, a thermometer and a condenser, start stirring, then slowly add the emulsion, continue stirring to mix evenly, raise the temperature to 60°C, and then slowly add the potassium persulfate solution. After the addition is complete, raise the temperature to 75°C and keep warm for 3 hours. During this period, continue stirring at 100 r / min. When the system begins to show a gel state, stop heating and stirring, cool naturally to room temperature, filter the gel product, wash it with pure water three times, transfer it to a vacuum drying oven, and dry it at 50°C to constant weight to obtain a compatibilizer.
[0063] The potassium persulfate solution is prepared by mixing 0.5 g of potassium persulfate and 20 g of pure water.
[0064] Example 1 The present embodiment provides a PPHM corrugated pipe, including 10 kg of polypropylene resin, 0.4 kg of modified mica sheets, 0.7 kg of modified carbon fibers, 1 kg of a compatibilizer, 0.5 kg of a low-temperature resistant agent, and 0.08 kg of an antioxidant.
[0065] Among them, the modified mica flakes come from Preparation Example 1, the modified carbon fibers come from Preparation Example 4, the compatibilizer comes from Preparation Example 7, the low-temperature resistant agent is ethylene-vinyl acetate copolymer, the mass fraction of vinyl acetate in the ethylene-vinyl acetate copolymer is 12%, and the antioxidant is antioxidant 1010.
[0066] This embodiment also provides a method for preparing the above-mentioned PPHM bellows, comprising the following steps: S1: 5kg of polypropylene resin and 1kg of compatibilizer were placed in a high-speed mixer for preliminary blending at a speed of 800r / min for 12min, and then 5kg of polypropylene resin, 0.4kg of modified mica flakes, 0.7kg of modified carbon fiber, 0.5kg of low-temperature resistant agent and 0.08kg of antioxidant were added, the speed was adjusted to 600r / min, and mixed for 5min, then the speed was adjusted to 800r / min, and mixed for 10min, and then the speed was adjusted to 1000r / min, and mixed for 10min to obtain an extrudate; S2: Add the extrudate into a twin-screw extruder with a screw speed of 180r / min. The barrel of the twin-screw extruder from the feed port to the extrusion die is set as Zone I, Zone II, Zone III and Zone IV in sequence. The temperature of Zone I is set at 155-165°C, the temperature of Zone II is set at 165-175°C, the temperature of Zone III is set at 175-185°C, and the temperature of Zone IV is set at 185-195°C. After the material is extruded from the die, it immediately enters the vacuum sizing device with a vacuum degree of -0.03Mpa~-0.05Mpa. After that, it is cooled and shaped at a wind speed of 8m / s. After cutting and quality inspection according to specifications, the PPHM corrugated pipe can be obtained.
[0067] Example 2 The present embodiment provides a PPHM corrugated pipe, including 10 kg of polypropylene resin, 0.7 kg of modified mica sheets, 0.9 kg of modified carbon fibers, 1.3 kg of a compatibilizer, 1 kg of a low-temperature resistant agent, and 0.09 kg of an antioxidant.
[0068] Among them, the modified mica flakes come from Preparation Example 1, the modified carbon fibers come from Preparation Example 4, the compatibilizer comes from Preparation Example 7, the low-temperature resistant agent is ethylene-vinyl acetate copolymer, the mass fraction of vinyl acetate in the ethylene-vinyl acetate copolymer is 12%, and the antioxidant is antioxidant 1010.
[0069] This embodiment also provides a method for preparing the above-mentioned PPHM bellows, comprising the following steps: S1: 5kg of polypropylene resin and 1.3kg of compatibilizer were placed in a high-speed mixer for preliminary blending at a speed of 800r / min for 15min, and then 5kg of polypropylene resin, 0.7kg of modified mica flakes, 0.9kg of modified carbon fiber, 1kg of low-temperature resistant agent and 0.09kg of antioxidant were added, the speed was adjusted to 600r / min, and mixed for 6min, then adjusted to 800r / min, mixed for 12min, and then adjusted to 1000r / min, mixed for 12min to obtain an extrudate; S2: Add the extrudate into a twin-screw extruder with a screw speed of 190r / min. The barrel of the twin-screw extruder from the feed port to the extrusion die is set as Zone I, Zone II, Zone III and Zone IV in sequence. The temperature of Zone I is set at 155-165°C, the temperature of Zone II is set at 165-175°C, the temperature of Zone III is set at 175-185°C, and the temperature of Zone IV is set at 185-195°C. After the material is extruded from the die, it immediately enters the vacuum sizing device with a vacuum degree of -0.03Mpa~-0.05Mpa. After that, it is cooled and shaped at a wind speed of 8m / s. After cutting and quality inspection according to specifications, the PPHM corrugated pipe can be obtained.
[0070] Example 3 The present embodiment provides a PPHM corrugated pipe, including 10 kg of polypropylene resin, 1 kg of modified mica sheets, 1.2 kg of modified carbon fibers, 1.5 kg of a compatibilizer, 1.5 kg of a low-temperature resistant agent, and 0.1 kg of an antioxidant.
[0071] Among them, the modified mica flakes come from Preparation Example 1, the modified carbon fibers come from Preparation Example 4, the compatibilizer comes from Preparation Example 7, the low-temperature resistant agent is ethylene-vinyl acetate copolymer, the mass fraction of vinyl acetate in the ethylene-vinyl acetate copolymer is 12%, and the antioxidant is antioxidant 1010.
[0072] This embodiment also provides a method for preparing the above-mentioned PPHM bellows, comprising the following steps: S1: 5kg of polypropylene resin and 1.5kg of compatibilizer were placed in a high-speed mixer for preliminary blending at a speed of 800r / min for 20min, and then 5kg of polypropylene resin, 1kg of modified mica flakes, 1.2kg of modified carbon fiber, 1.5kg of low-temperature resistant agent and 0.1kg of antioxidant were added, the speed was adjusted to 600r / min, and mixed for 7min, then adjusted to 800r / min, mixed for 15min, and then adjusted to 1000r / min, mixed for 15min to obtain an extrudate; S2: Add the extrudate into a twin-screw extruder with a screw speed of 200r / min. The barrel of the twin-screw extruder from the feed port to the extrusion die is set as Zone I, Zone II, Zone III and Zone IV in sequence. The temperature of Zone I is set to 155-165°C, the temperature of Zone II is set to 165-175°C, the temperature of Zone III is set to 175-185°C, and the temperature of Zone IV is set to 185-195°C. After the material is extruded from the die, it immediately enters the vacuum sizing device with a vacuum degree of -0.03Mpa~-0.05Mpa. After that, it is cooled and shaped at a wind speed of 8m / s. Cutting and quality inspection are performed according to specifications to obtain the PPHM corrugated pipe.
[0073] Example 4 The difference between this embodiment and embodiment 2 is that: The modified mica flakes are from Preparation Example 2, the modified carbon fibers are from Preparation Example 5, the compatibilizer is from Preparation Example 8, the low temperature resistant agent is ethylene-vinyl acetate copolymer, and the mass fraction of vinyl acetate in the ethylene-vinyl acetate copolymer is 18%.
[0074] The rest is the same as in Example 2.
[0075] Example 5 The difference between this embodiment and embodiment 2 is that: The modified mica sheet comes from Preparation Example 3, the modified carbon fiber comes from Preparation Example 6, the compatibilizer comes from Preparation Example 9, the low temperature resistant agent is ethylene-vinyl acetate copolymer, and the content of vinyl acetate in the ethylene-vinyl acetate copolymer is 25%.
[0076] The rest is the same as in Example 2.
[0077] Example 6 The difference between this embodiment and embodiment 1 is that: The content of vinyl acetate in ethylene-vinyl acetate copolymer is 32%.
[0078] Example 7 The difference between this embodiment and embodiment 5 is that: The modified mica flakes are from Preparation Example 1, the modified carbon fibers are from Preparation Example 4, the compatibilizer is from Preparation Example 9, and the low-temperature resistant agent includes ethylene-vinyl acetate copolymer and styrene-butadiene-styrene block copolymer, and the mass fraction of vinyl acetate in the ethylene-vinyl acetate copolymer is 25%.
[0079] The amount of ethylene-vinyl acetate copolymer used was 0.2 kg, and the amount of styrene-butadiene-styrene block copolymer used was 0.8 kg.
[0080] The rest is the same as Example 5.
[0081] Example 8 The present embodiment provides a PPHM corrugated pipe, including 10 kg of polypropylene resin, 0.7 kg of modified mica sheets, 0.9 kg of modified carbon fibers, 1.3 kg of a compatibilizer, 1 kg of a low temperature resistant agent, 0.09 kg of an antioxidant, and 0.2 kg of calcium chloride.
[0082] The modified mica flakes are from Preparation Example 1, the modified carbon fibers are from Preparation Example 4, the compatibilizer is from Preparation Example 9, the low temperature resistant agent includes ethylene-vinyl acetate copolymer and styrene-butadiene-styrene block copolymer, the mass fraction of vinyl acetate in the ethylene-vinyl acetate copolymer is 25%, and the antioxidant is antioxidant 1010.
[0083] The amount of ethylene-vinyl acetate copolymer used was 0.4 kg, and the amount of styrene-butadiene-styrene block copolymer used was 0.6 kg.
[0084] This embodiment also provides a method for preparing the above-mentioned PPHM bellows, comprising the following steps: S1: 5kg of polypropylene resin and 1.3kg of compatibilizer were placed in a high-speed mixer for preliminary blending at a speed of 800r / min for 15min, and then 5kg of polypropylene resin, 0.7kg of modified mica flakes, 0.9kg of modified carbon fiber, 1kg of low-temperature resistant agent, 0.09kg of antioxidant and 0.5kg of calcium chloride were added, the speed was adjusted to 600r / min, and mixed for 6min, then the speed was adjusted to 800r / min, and mixed for 12min, and then the speed was adjusted to 1000r / min, and mixed for 12min to obtain an extrudate; S2: Add the extrudate into a twin-screw extruder with a screw speed of 190r / min. The barrel of the twin-screw extruder from the feed port to the extrusion die is set as Zone I, Zone II, Zone III and Zone IV in sequence. The temperature of Zone I is set at 155-165°C, the temperature of Zone II is set at 165-175°C, the temperature of Zone III is set at 175-185°C, and the temperature of Zone IV is set at 185-195°C. After the material is extruded from the die, it immediately enters the vacuum sizing device with a vacuum degree of -0.03Mpa~-0.05Mpa. After that, it is cooled and shaped at a wind speed of 8m / s. After cutting and quality inspection according to specifications, the PPHM corrugated pipe can be obtained.
[0085] Wherein, the calcium chloride is pretreated calcium chloride, and the preparation method of pretreated calcium chloride comprises the following steps: S11: 0.3 kg of calcium chloride was placed in a drying oven at 120° C. for 2 h, then ground and crushed until it completely passed through a 20-mesh Taylor standard sieve (particle size not higher than 0.9 mm), then immersed in 600 g of a 1.5% KH-550 aqueous solution, stirred and mixed for 2.5 h, centrifuged and filtered, then placed in a drying oven at 120° C. for 4 h, and lightly ground and dispersed until it completely passed through a 20-mesh Taylor standard sieve to obtain primary calcium chloride; S12: Prepare a 20% mass fraction of bisphenol A epoxy resin solution, the solvent is acetone, slowly add primary calcium chloride to the bisphenol A epoxy resin solution, the mass ratio of calcium chloride to bisphenol A epoxy resin solution is 1:3, use a high-speed agitator with a speed of 1000r / min, mix for 60min, dry at 80°C until there is no obvious moisture, transfer to a drying oven, dry at 50°C for 30min, lightly grind and disperse, and obtain pretreated calcium chloride.
[0086] Example 9 The difference between this embodiment and embodiment 8 is that: The amount of calcium chloride used is 0.4 kg.
[0087] Wherein, the calcium chloride is pretreated calcium chloride, and the preparation method of pretreated calcium chloride comprises the following steps: S11: 0.5 kg of calcium chloride was placed in a drying oven at 120° C. for 3 h, then ground and crushed until it completely passed through a 20-mesh Taylor standard sieve (particle size not higher than 0.9 mm), then immersed in 1000 g of a 2% KH-550 aqueous solution, stirred and mixed for 1.5 h, centrifuged and filtered, then placed in a drying oven at 120° C. for 5 h, and lightly ground and dispersed until it completely passed through a 20-mesh Taylor standard sieve to obtain primary calcium chloride; S12: Prepare a 25% mass fraction of bisphenol A epoxy resin solution, the solvent is acetone, slowly add primary calcium chloride to the bisphenol A epoxy resin solution, the mass ratio of calcium chloride to bisphenol A epoxy resin solution is 1:5, use a high-speed agitator with a speed of 1000r / min, mix for 40min, dry at 80°C until there is no obvious moisture, transfer to a drying oven, dry at 50°C for 30min, lightly grind and disperse, and obtain pretreated calcium chloride.
[0088] The rest is the same as Example 8.
[0089] Example 10 The present embodiment provides a PPHM corrugated pipe, including 10 kg of polypropylene resin, 0.7 kg of modified mica sheets, 0.9 kg of modified carbon fibers, 1.3 kg of a compatibilizer, 1 kg of a low-temperature resistant agent, 0.09 kg of an antioxidant, 0.8 kg of calcium chloride, and 0.05 kg of glycerol.
[0090] The modified mica flakes are from Preparation Example 1, the modified carbon fibers are from Preparation Example 4, the compatibilizer is from Preparation Example 9, the low temperature resistant agent includes ethylene-vinyl acetate copolymer and styrene-butadiene-styrene block copolymer, the mass fraction of vinyl acetate in the ethylene-vinyl acetate copolymer is 25%, and the antioxidant is antioxidant 1010.
[0091] The amount of ethylene-vinyl acetate copolymer used was 0.4 kg, and the amount of styrene-butadiene-styrene block copolymer used was 0.6 kg.
[0092] This embodiment also provides a method for preparing the above-mentioned PPHM bellows, comprising the following steps: S1: 5kg of polypropylene resin and 1.3kg of compatibilizer were placed in a high-speed mixer for preliminary blending at a speed of 800r / min for 15min, and then 5kg of polypropylene resin, 0.7kg of modified mica flakes, 0.9kg of modified carbon fiber, 1kg of low-temperature resistant agent, 0.09kg of antioxidant, 0.8kg of calcium chloride and 0.05kg of glycerol were added, the speed was adjusted to 600r / min, mixed for 6min, then adjusted to 800r / min, mixed for 12min, and then adjusted to 1000r / min, mixed for 12min to obtain an extrudate; S2: Add the extrudate into a twin-screw extruder with a screw speed of 190r / min. The barrel of the twin-screw extruder from the feed port to the extrusion die is set as Zone I, Zone II, Zone III and Zone IV in sequence. The temperature of Zone I is set at 155-165°C, the temperature of Zone II is set at 165-175°C, the temperature of Zone III is set at 175-185°C, and the temperature of Zone IV is set at 185-195°C. After the material is extruded from the die, it immediately enters the vacuum sizing device with a vacuum degree of -0.03Mpa~-0.05Mpa. After that, it is cooled and shaped at a wind speed of 8m / s. After cutting and quality inspection according to specifications, the PPHM corrugated pipe can be obtained.
[0093] Embodiment 11 The difference between this embodiment and embodiment 10 is that: The dosage of glycerol is 0.15 kg; The rest is the same as Example 10.
[0094] Comparative Example 1 The difference between this comparative example and Example 1 is: Mica flakes are unmodified.
[0095] The rest is the same as in Example 1.
[0096] Comparative Example 2 The difference between this comparative example and Example 1 is: The carbon fiber is unmodified.
[0097] The rest is the same as in Example 1.
[0098] Comparative Example 3 The difference between this comparative example and Example 1 is: The compatibilizer is maleic anhydride grafted polypropylene.
[0099] The rest is the same as in Example 1.
[0100] Performance Testing The corrugated pipes prepared in Examples 1 to 11 and Comparative Examples 1 to 3 have a diameter of 200 mm and a thickness of 5 mm; refer to the detection method disclosed in GB / T35451.1-2017 "Polypropylene (PP) structural wall pipe system for buried drainage and sewage", and cut appropriate samples to detect their performance at room temperature and low temperature.
[0101] Ring stiffness test: The sample length is usually 300mm, and the number of ring stiffness test samples is 5; Tensile strength test: Take dumbbell-shaped specimens, the diameter of the middle part is 10mm, the diameter of both ends is 20mm, the length of the middle part is 50mm, the total length is 70mm, the transition angle is about 45°, and the number of tensile strength test specimens is 5; Impact resistance test: The sample length is 300mm, the impact height is 200cm, the falling weight is 1.6kg, and each group of impact resistance test samples is 15.
[0102] (1) Normal temperature test: Place 20 test specimens in a test environment at about 23±2℃ for 3 hours, then conduct the test and record the test results.
[0103] (2) Low temperature test: Place 15 test specimens in a test chamber, adjust the temperature of the test chamber to -20°C, and keep it warm for 3 hours. After taking them out, test them in an environment of -20±2°C and record the test results.
[0104] Table 1 Performance test data of bellows of Examples 1 to 11 and Comparative Examples 1 to 3
[0105] Analysis of the performance test data in Table 1 shows that: It can be seen from Example 1 and Comparative Examples 1 to 3 that: first, the mica flakes and carbon fibers are not modified, and the ring stiffness, tensile strength and impact performance of the bellows are poor. This is mainly because the mica flakes and carbon fibers cannot be evenly dispersed in the polypropylene resin without modification, and the interface bonding between the polypropylene resin and other components is poor, and it is easy to slip in the polypropylene resin, or even slide out, and it is impossible to effectively transfer or share stress, so that the ring stiffness, tensile strength and impact performance are poor.
[0106] Secondly, after replacing the compatibilizer in this application with commercially available maleic anhydride grafted polypropylene, the ring stiffness and tensile strength are reduced, and the impact resistance is also slightly worse. This may be because: the compatibilizer in this application makes the modified carbon fiber, modified mica sheet and polypropylene resin closely combined with each other, which not only optimizes the stress transfer path, but also enables the various parts of the corrugated pipe to work synergistically when subjected to force; during the stretching process, the various components can better share the tensile stress due to their good combination and give full play to their respective reinforcement effects.
[0107] As shown in Examples 1 to 3, by increasing the amount of modified carbon fiber, modified mica sheet, compatibilizer, low temperature resistant agent, etc. within a certain range, the obtained bellows ring stiffness gradually increases, but the tensile strength decreases. This is mainly due to: although modified carbon fiber can enhance the ring stiffness of the bellows, the interfacial bonding force between modified carbon fiber and polypropylene resin is limited. When the amount is too much, under the action of tensile stress, some modified carbon fibers may not be able to effectively transfer stress to the matrix, but are pulled out from the polypropylene resin. This leads to a reduction in the part that effectively bears tensile stress during the stretching process, thereby reducing the tensile strength. In addition, increasing the amount of modified carbon fiber and modified mica sheet may form more interfaces inside the bellows. These interfaces are prone to become stress concentration points during the stretching process. When tensile stress acts on the bellows, stress will preferentially accumulate at these interfaces, resulting in excessive local stress, thereby more easily inducing the generation and expansion of cracks, reducing tensile strength.
[0108] It can be seen from Examples 1 to 2 and Examples 4 to 6 that by adopting different preparation examples to prepare modified carbon fibers, modified mica sheets and compatibilizers and optimizing the types of low-temperature resistant agents, the ring stiffness, tensile strength and impact resistance of the prepared bellows are all maintained in a good range. It is explained that after the various components (modified carbon fibers, modified mica sheets, compatibilizers and low-temperature resistant agents) are targetedly improved and optimized through different preparation examples, they form an overall system with good synergy.
[0109] When the proportion of vinyl acetate in ethylene-vinyl acetate copolymer increases to a certain level, the ring stiffness and tensile strength of the produced bellows are slightly reduced. This is mainly because: when the proportion of vinyl acetate increases, on the one hand, the flexibility of the molecular chain increases, the crystallinity decreases, and the rigid part decreases, which causes the bellows to bend and deform easily when subjected to external radial pressure, and also affects the stress transfer path.
[0110] As shown in Examples 7 to 9, by further compounding pretreated calcium chloride, the ring stiffness, tensile strength and impact resistance of the prepared bellows are all improved. This is because the pretreated calcium chloride forms a good interface bond with the polypropylene resin, so that stress can be effectively transmitted, and its own rigidity can change the expansion direction of the crack or consume the energy of crack expansion, making it difficult for the crack to continue to extend, thereby improving the tensile strength of the bellows. At the same time, it can also play its filling role, uniformly fill the internal space of the bellows, and effectively reduce the defects such as gaps and holes that may exist inside the bellows. In addition, the bisphenol A type epoxy resin coated on its outer layer not only further enhances the interface compatibility with the polypropylene resin, but also provides additional toughness and strength support for the bellows.
[0111] It can be seen from Examples 9 to 11 that by further compounding propylene glycol, the ring stiffness of the bellows obtained is reduced, but the tensile strength is improved. This may be due to the fact that the addition of propylene glycol makes the molecular chain easier to slide and deform, just like adding a lubricant to the originally tight molecular chain structure, so that the bellows cannot maintain a stable shape as before when subjected to radial pressure, resulting in a decrease in ring stiffness. However, the polymer molecular chain moves more smoothly when subjected to force, which can reduce the generation of stress concentration points, so that the stress can be more evenly distributed in the bellows, rather than concentrated in certain weak parts, so that the bellows can better cooperate to withstand the tensile force when stretched, thereby improving the tensile strength.
Claims
1. A PPHM bellows, characterized in that: The PPHM corrugated pipe comprises 100 parts by mass of polypropylene resin, 4 to 10 parts by mass of mica sheets, 7 to 12 parts by mass of carbon fibers, 10 to 15 parts by mass of a compatibilizer, 5 to 15 parts by mass of a low temperature resistant agent, and 0.8 to 1 part by mass of an antioxidant; The mica sheet is a modified mica sheet, and the carbon fiber is a modified carbon fiber; the low temperature resistant agent is at least one of ethylene-vinyl acetate copolymer and styrene-butadiene-styrene block copolymer; The preparation method of the compatibilizer comprises the following steps: uniformly mixing polypropylene powder, dibutyl maleate, hydroxyethyl acrylate, potassium persulfate and a solvent, heating to 70-80° C., reacting for 2-4 hours, cooling, solid-liquid separation, washing, and drying to obtain the compatibilizer, wherein the mass ratio of the polypropylene powder, dibutyl maleate and hydroxyethyl acrylate is 1:0.2-0.4:0.2-0.
4.
2. The PPHM bellows according to claim 1, characterized in that: The preparation method of the modified mica sheet comprises the following steps: The mica flakes are uniformly dispersed in the sodium hexametaphosphate solution, and plasma treatment is performed for 10-20 minutes at a power of 200-300 W under an inert atmosphere. An initiator and propylene oxide are added, and the mixture is uniformly mixed. The mixture is heated to 70-90° C. and kept warm for 4-6 hours. The mixture is cooled, solid-liquid separation is performed, the mixture is washed, and the mixture is dried to obtain the modified mica flakes.
3. The PPHM bellows according to claim 1, characterized in that: The preparation method of the modified carbon fiber comprises the following steps: (1) Immersing the carbon fiber in a potassium permanganate solution, mixing for 2 to 4 hours, separating the solid and the liquid, washing, and then immersing the carbon fiber in a potassium persulfate solution, mixing for 1.5 to 2.5 hours, separating the solid and the liquid, washing, to obtain pretreated carbon fiber; (2) uniformly mixing acrylic acid, hydroxyethyl acrylate, styrene and a solvent to obtain a mixed emulsion; (3) Under an inert atmosphere, the pretreated carbon fiber, the redox initiator and the mixed emulsion are mixed evenly, the temperature is raised to 70-90°C, the temperature is kept for 4-6 hours, the temperature is lowered, the solid-liquid separation is performed, the mixture is washed and dried to obtain the modified carbon fiber.
4. The PPHM bellows according to claim 1, characterized in that: The content of vinyl acetate in the ethylene-vinyl acetate copolymer is 12% to 25%.
5. The PPHM bellows according to claim 4, characterized in that: The PPHM bellows also includes 2 to 8 parts by mass of calcium chloride.
6. The PPHM bellows according to claim 5, characterized in that: The calcium chloride is obtained through the following pretreatment steps: S11: crushing and sieving calcium chloride, then immersing it in a silane coupling agent solution, mixing it for 1.5 to 2.5 hours, separating the solid from the liquid, drying it, and sieving it to obtain primary calcium chloride; S12: mixing primary calcium chloride with 20% to 25% by mass of bisphenol A epoxy resin solution for 40 to 60 minutes, drying, and dispersing to obtain pretreated calcium chloride.
7. The PPHM bellows according to claim 6, characterized in that: The PPHM bellows also includes 0.5-1.5 parts by mass of propylene glycol.
8. A method for preparing a PPHM corrugated pipe according to any one of claims 1 to 4, characterized in that: The steps include: S1: premixing a compatibilizer and a portion of polypropylene resin uniformly, then adding modified mica flakes, modified carbon fiber, a low temperature resistant agent and another portion of polypropylene resin, and mixing uniformly to obtain an extrudate; S2: Add the extrudate into the extruder and extrude, size, cool, cut and inspect the quality to obtain the PPHM corrugated pipe.
9. The method for preparing the PPHM corrugated pipe according to claim 8, characterized in that: In step S1, after adding the low-temperature resistant agent, the step of adding calcium chloride is also included.
10. The method for preparing the PPHM corrugated pipe according to claim 9, characterized in that: In step S1, after adding calcium chloride, the step of adding glycerol is also included.
Citation Information
Patent Citations
Raw material composition for preparing heavy caliber polypropylene double-wall corrugated pipe
CN101983982A
Cited By
Reinforced and toughened CM square electric corrugated pipe and preparation method thereof
CN122011593A